Solitary Fibrous Tumor of the Postcricoid Region: A Case Report and Literature Review - Brian Cervenka; Brenda Villegas; Uttam Sinha (Case Reports in Otolaryngology)
Solitary fibrous tumor (SFT) is a rare mesenchymal neoplasm that can present essentially anywhere in the body. Presentations in the hypopharynx are extremely rare with only two previous cases reported. We report the first case of postcricoid SFT occurring in a 58-year-old male requiring a microsuspension laryngoscopy excision following an unsuccessful transoral robotic attempt. The excision was uneventful, and the patient is currently without recurrence. Current management strategies of the hypopharyngeal SFT, the unique differential diagnosis, and challenges in surgical approaches in the postcricoid region are discussed.